STRENGTHENING BUSINESS GROWTH MODEL FOR COOPERATIVES THROUGH THE IMPLEMENTATION OF SHARIAH-BASED QUALITY MANAGEMENT STANDARD MS1900:2014 - Ahmad Bustamam, Ummi Salwa; Sabri, Hisham; Abu Hassan, Hasrin (I-iECONS e-proceedings, 2023)
A standard is an agreed-upon, reproducible procedure. Islam provides guidelines for applying a noble standard in daily life, in addition to guidance for business organizations. Malaysian Standard (MS) 1900:2014 is a standard that specifies the requirements for a Quality Management System that complies with shariah. The advantages of the MS 1900:2014 Shariah-based Quality Management System ensure that the universal values of justice, honesty, veracity, sincerity, punctuality, and discipline are incorporated into the quality management practices. In addition, it will place a greater emphasis on ethical standards in business operations. Finally, the organization will receive independent confirmation that its processes and practices adhere to Shariah principles. In 2008, only five companies obtained this certification, and ten more in 2011. In 2012, after one year, approximately 18 organizations had obtained the MS1900:2005 certification. Presently, approximately forty organizations have attained MS1900:2014 certification. Increasing numbers annually demonstrate the significance and vigilance of implementing Islamic principles in business organizations. Despite this, the number is still minuscule in comparison to the vast number of businesses in Malaysia, including cooperatives. An in-depth understanding of how organizations, in particular Cooperatives, could utilize the Shariah-based quality management system MS1900:2014 to enhance business growth was pursued using a case study approach. Eight major Cooperatives from the Top 100 List in 2021 were interviewed for elucidation on the topic of the study. SIRIM was also contacted to obtain additional information about the standard. The study's findings contribute to the body of knowledge, particularly in the area of quality management system, as well as to the practice, primarily through a better understanding of how cooperatives can enhance their business growth by implementing the Shariah-based Quality Management System MS1900:2014. This will result in enduring economic growth.